EVALUATION OF FOUR INTEGRATED PEST MANAGEMENT PACKAGES FOR CONTROLLING MAIN PESTS OF COTTON IN RAINFED FIELDS - Nurindah Nurindah; Dwi Adi Sunarto (Indonesian Journal of Agricultural Science, 2014)
Cotton production nationally is low due to various constraints, including pests. Two main pests commonly found in cotton plantation in rain fed fields are cotton leafhopper (Amrasca biguttula) and cotton bollworm (Helicoverpa armigera). The study aimed to evaluate four packages of integrated pest management (IPM) techniques to control cotton leafhopper and cotton bollworm in rain fed fields. The experiment was conducted in farmers’ fields at Asembagus, East Java, between January and July 2012. Four packages of IPM evaluated were cotton varieties, i.e. Kanesia 10 or Kanesia 13, and seed treatment with synthetic insecticide (imidacloprid) before sowing or spraying molasses (10 ml L-1 water) as food for natural enemies. The cotton plants were intercropped with groundnut and sprayed with neem seed extract (NSE) at the action threshold level for pest control. These packages were compared among themselves and also with the methods usually used by farmers, i.e. planting cotton variety Kanesia 8 intercropped with groundnut and pest control using synthetic chemical insecticides. Twenty five plants were sampled randomly per plot and measured for their growth, leafhopper and  bollworm populations, as well as cotton seed yield per plot. Observations were made weekly, starting at 30 days after planting (DAP) until 120 DAP. The results showed that the use of Kanesia 10 or Kanesia 13 intercropped with groundnut and spraying molasses to conserve natural enemies was the best  pest management practice and superior to farmers’ practices. Conserving natural enemies is not only profitable (saving production cost of IDR1,150,000 to IDR1,500,000 ha-1 season-1), but also safe for the environment (no need to spray chemical insecticides).